PENDIDIKAN KESEHATAN TENTANG CARA PENGOLAHAN SAMPAH DI LINGKUNGAN MASYARAKAT DI DESA CITANGTU KECAMATAN WANARAJA GARUT - Aceng Ali Awaludin; Elang Mohamad Atoilah; Eti Suliyawati; Eva Daniati; Gin Gin Sugih Permana; Novie Melliasany (LP4M STIKes Karsa Husada Garut, 2021)
Environmental problems are a decrease in the carrying capacity of the environment as a result of low public awareness of the importance of environmental management. This is caused by several factors, including: changes in the function and arrangement of the environment, a decrease in the carrying capacity and quality of the environment, the lack of integration in the management of human, natural and artificial resources in environmental management between various parties, the less than optimal utilization of urban space, and environmental pollution. generated by waste. The purpose of community service in addition to reducing waste is also to provide solutions in reducing community environmental pollution in the form of organic waste, creating a healthy and comfortable community environment, increasing community income by selling products from processing organic waste in the form of compost. The method used was lectures, discussions and questions and answers as well as waste management practices which were attended by 42 participants. The results obtained from this activity produce several products from processed waste in the form of doormats, bags and other recycled products. The conclusions obtained from the activities of processing household waste/waste into materials of economic value in the form of providing theoretical and practical counseling to PKK mothers in Citangtu Village, Wanaraja Garut District, received a very good response. The provision of counseling materials interspersed with motivation for entrepreneurship makes the mothers more enthusiastic and this activity can continue to improve the welfare and standard of living of the residents.